Harmfulness Evaluation Method for On-Board Water Ballast Management - Kurtela, Željko; Komadina, Pavao (Promet - Traffic&Transportation, 2009)
Having identified all the dominant factors and having puttogether a mosaic of all the factors resulting from a ship 's voyage,as well as a number of differently dimensioned criteria, theharmfulness evaluation method for water ballast managementon board has been elaborated. By careful analysis of the impactfactors to which status elements are adjoined, by the assignmentof harmfulness levels to the status elements, by determiningdifficulty factor values, by introduction of treatment methodsi.e. exchange of water ballast, certain characteristic managementscenarios according to ship type are developed. Cumulativescenarios provide insight into the total harmfulness ofwater ballast management. The introduction of a comprehensiveapproach results in the development of different scenariosapplicable to all ships. The established harmfulness evaluationmethod for water ballast management is applicable to all shiptypes, and it has been tested on various types of ships that weredischarging ballast in various ports worldwide.